Pendidikan Multikultural Sebagai Strategi Pencegahan Konflik Sosial di Masyarakat Heterogen - Nailatur Rizqiyah; Masti Yanto; Waqi’atul Masrurah; Saiful Arif (Jurnal Ilmiah Literasi Indonesia, 2025)
Indonesia is a pluralistic country with social and cultural diversity. This diversity can trigger conflicts that lead to national disintegration. Therefore, education should play a role in resolving and preventing conflicts in society. The purpose of writing this article is to explore more deeply the role of education, especially multicultural education, in preventing social conflicts in society. The method used in this study is a descriptive-analytical library research. Data collection was carried out through document analysis, by reviewing books and journal articles that are relevant to the topic discussed. The results of this study indicate that multicultural education can function as an alternative means of preventing social conflict. Multicultural education is an education that teaches attitudes of respecting and honoring differences. With multicultural education, it can certainly increase tolerance in students from an early age, and this can minimize the occurrence of conflict in society.